PELATIHAN PENYUSUNAN LAPORAN KEUANGAN USAHA BERBASIS MICROSOFT EXCEL PADA PELAKU UMKM, DESA MOJODESO, BOJONEGORO - Untarini, Nindria; Asandimitra, Nadia; Frianto, Agus; Tiarawati, Monika (Universitas Mataram, 2024)
Financial statements are crucial for owners of Micro, Small, and Medium Enterprises (MSMEs) as they serve as evidence that the MSMEs exhibit sound financial performance and reliability, thereby enhancing the confidence of banks in extending business credit or capital to them. However, approximately 72 % of MSMEs in Indonesia still lack access to capital from both banks and non-bank financial institutions. The obstacle lies in the inability of MSMEs to manage their finances in an organized and periodic manner. Hence, there is a need for education and introductions on how to prepare financial statements that are easy and effective for MSME practitioners. The objective of this Community Service Program (PKM) is to provide education and training on the preparation of financial statements based on Ms Excel for MSME practitioners in the food and beverage sector affiliated with the Creative Economy Center (CEC) community in Mojodeso village, Kapas district, Bojonegoro regency. The activity took place at the Mojodeso Village Hall in Bojonegoro, with a total of 15 MSME participants. The stages of this activity include planning, implementation, and evaluation. Data were analyzed descriptively using percentage techniques. The results of the activity indicate that the training on the preparation of financial statements based on Ms Excel has enhanced the understanding and skills of MSME practitioners in recording financial statements. Monitoring and evaluation activities were conducted to ensure that participants could correctly and regularly practice recording business financial statements MS Excel, as evidenced by the submission of soft copies of financial statements in Ms Excel format to the PKM team. The conclusion of this PKM is that the training activity effectively improved the understanding and skills in the practical creation of business financial statements based on MsExcel.